Conceptual approaches to an integration model for interaction between banking and enterprise it systems based on service-oriented architecture (Economics and region, 2025)
The contemporary digital landscape is characterized by rapid changes, compelling both banking institutions and enterprises to seek new pathways for enhancing efficiency and competitiveness. Digital transformation has ceased to be merely a trend, evolving into a fundamental prerequisite for survival and development. Banks are actively moving away from traditional service delivery models, striving to become more agile, customer-centric, and integrated into the daily lives of their customers. Simultaneously, enterprises require real-time access to financial information and the capability to embed banking services directly into their own operational processes. One of the key catalysts for these changes is the development of the «API economy». This concept fundamentally alters the approaches to the creation, provision, and consumption of financial services, transforming banking from a physical location into a service available anywhere and anytime. Such an approach opens significant opportunities for innovation, enabling banks and enterprises to create new products and services by combining their own capabilities with third-party services. Traditional IT system integration methods, particularly point-to-point integration, are proving to be inefficient in the face of today's dynamic demands. Such approaches are characterized by high complexity, significant maintenance costs, limited scalability, and often lead to the formation of isolated data silos. This complicates obtaining a holistic view of business processes and customers and hinders the implementation of innovations. There is an acute need for architectures that support flexibility, component reusability, and simplified integration of heterogeneous systems, which are often supplied by different vendors and possess distinct architectural patterns. The drive for integration is motivated not only by technical requirements but also represents a strategic business necessity. Enterprises seek to optimize operational processes, automate data reconciliation, and gain real-time access to financial information.
Keywords: enterprise; bank; SOA; API; model; architecture